Opioid Use After Laparoscopic Hysterectomy: Prescribing Practices and Preoperative Predictors [5Q]. (May 2018) - Wong, Marron C.; Isaacson, Keith B.; Morris, Stephanie
Abstract : INTRODUCTION: Gynecologists can address the prescription opioid epidemic by prescribing appropriate quantities of postoperative opioids. Our goals were to measure opioid use after laparoscopic hysterectomy (LH) and to survey patients to identify factors that are predictive of higher opioid use. METHODS: We prospectively followed 60 patients undergoing LH for benign indications. Patients completed a preoperative survey including demographics, medical history, and standardized surveys measuring pain catastrophizing (PCS), anxiety (GAD-7), and depression (PHQ-9). Pain scores and pain medication usage were assessed at one and two weeks after surgery. Postoperative opioids were converted to morphine milligram equivalents (MME). Non-parametric statistical methods (Spearman correlation coefficient or Wilcoxon rank-sum test) were used to test for correlations between predictors and postoperative MME. RESULTS: A median of 20 opioid pills were prescribed (150 MME). Median use was 37.5 MME, equivalent to 5 tabs of 5mg oxycodone. 30% used opioids for <24 hours; 90% used no opioids after one week. 88.3% had leftover opioids (median 15 pills). Only 22.6% of leftover opioids were stored securely. Factors that were significantly associated (p<0.005) with increased opioid use included preoperative pain score, expected postoperative pain level, predicted pain medication requirement, PCS, GAD-7, PHQ-9, history of endometriosis or pelvic pain, preoperative pain medication use, and smaller uterine size. CONCLUSION: The average LH patient uses minimal opioids and leftover opioids are usually kept unsecured, illustrating a need to decrease prescribed opioids and educate patients about opioid disposal. Our preoperative survey shows promise for building a model to predict which patients are at risk for requiring more opioids.